2008
DOI: 10.1093/jnci/djn394
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Second Malignancies in Survivors of Retinoblastoma: More Than 40 Years of Follow-up

Abstract: Our analysis of middle-aged hereditary retinoblastoma survivors suggests that these individuals have an excess risk of epithelial cancer. Lifelong follow-up studies are needed to evaluate the full spectrum of subsequent cancer risk in hereditary retinoblastoma survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
253
6
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(284 citation statements)
references
References 35 publications
19
253
6
6
Order By: Relevance
“…MacCarthy et al [2] found in a cohort study that LMS is the most often reported secondary malignancy accounting for 58% of cases followed by other [1] found that LMS was the most represented of soft tissue sarcomas in patients with a history of RB, accounting for 33% of secondary tumors in a cohort study of 963 patients with RB. Interestingly, both in this study and supported by the study of Marees et al [6] it was found that LMS arose more commonly outside the field of prior radiation therapy, while the other subtypes more often arose inside the field. LMS tend to arise later after RB than other soft tissue sarcomas with 78% of LMS arose 30 years or more after initial diagnosis as compared to the majority of fibrosarcoma and rhabdomyosarcoma that arose within the first 20 years of diagnosis [1].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…MacCarthy et al [2] found in a cohort study that LMS is the most often reported secondary malignancy accounting for 58% of cases followed by other [1] found that LMS was the most represented of soft tissue sarcomas in patients with a history of RB, accounting for 33% of secondary tumors in a cohort study of 963 patients with RB. Interestingly, both in this study and supported by the study of Marees et al [6] it was found that LMS arose more commonly outside the field of prior radiation therapy, while the other subtypes more often arose inside the field. LMS tend to arise later after RB than other soft tissue sarcomas with 78% of LMS arose 30 years or more after initial diagnosis as compared to the majority of fibrosarcoma and rhabdomyosarcoma that arose within the first 20 years of diagnosis [1].…”
Section: Discussionsupporting
confidence: 86%
“…It has been suggested that the germline mutation predisposes to a lifelong increased risk of many forms of cancer [5]. Patients with hereditary RB have a higher cumulative risk of developing secondary malignancies than those with the non-hereditary form [2,6,7]. In one study, hereditary RB patients had an increased risk of secondary malignancy 40 years after RB treatment of approximately 28% as compared to 1.44% in patients with the nonhereditary form [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age of a second primary tumor is between 15 and 17 years old (20,22). However, increased risks of adult tumors such as epithelial cancers of the lung, bladder, and breast as well as uterine sarcomas have also been described (23,24).…”
Section: Hereditary Rb: Introductionmentioning
confidence: 99%
“…However, the toxicity of systemic chemotherapy, still represents an issue which deserves further investigation [76,77], particularly when genomic instability is involved, as in retinoblastoma [6,7]. In an effort to improve drug delivery to the tumour, and simultaneously reduce systemic toxicity, clinical researchers have more recently developed super selective Ophthalmic Artery Infusion (SOAI) of chemotherapeutic agents [78] which, although still controversial [79,80], promises a dramatic improvement in the rate of preservation of the affected eyes [81][82][83], particularly when different drugs are combined [84][85][86].…”
Section: Current Chemotherapy For Retinoblastoma and High Doses Of VImentioning
confidence: 99%